Incidence of Pelvic Inflammatory Disease Associated With Mycoplasma genitalium Infection: Evidence Synthesis of Cohort Study Data. (18th July 2020) - Lewis, Joanna; Horner, Paddy J; White, Peter J
Abstract: We synthesized evidence from the POPI sexual-health cohort study and estimated that 4.9% (95% credible interval, .4–14.1%) of Mycoplasma genitalium infections in women progress to pelvic inflammatory disease versus 14.4% (5.9–24.6%) of chlamydial infections. For validation, we predicted PID rates in 4 age groups that agree well with surveillance data.